Crack-healing investigation in asphalt mixture with modified thermoplasticbitumen composite - Mohd Suzeren Md Jamil,; Wan Naqiuddin Wan Zulrushdi,; Noor Nabilah Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to investigate the crack-healing of asphalt mixture by induction heating of bitumen-thermoplastic binder. This system employs a heterogeneous mixture, in which different percentages (2, 4, 6, and 8% by weigh) of thermoplastic healing agent (polyethylene (PE) and polypropylene (PP)) dissolve with the bitumen, respectively. Healing was achieved by heating the fractured asphalt composite to a specific temperature; in which heterogeneous blend has undergone random molecule diffusion and volumetric thermal expansion of healing agent within the matrix. The thermal properties in the bitumen-thermoplastic were characterized by means of dynamic mechanical thermal analysis (DMTA); in which the glass transition temperature (Tg ) has been used as a reference for the healing process. The FTIR shows no chemical reaction between bitumen and thermoplastic. Three-point bending test was conducted to demonstrate details crack-healing capability in asphalt composite. The results show that 6% of PE and PP to the mixture of bitumenthermoplastic has the highest tensile strength. The percentage of recovery was also measured through the healing cycle process using a three-point bending test. Overall, within the third healing cycle, asphalt composite with modified bitumen (with PP or PE) shows 98-55% of healing recovery. The best percentage recovery is using bitumen-PP mixture with a ratio of 94:6. The crack-healing process was also proven through the surface and cross-section asphalt morphology analyses using optical microscopy and scanning electron microscope (SEM).